ANALISA DEBIT ALIRAN FLUIDA TERHADAP EFEKTIFITAS RADIATOR PADA ENGINE MOBIL MAZDA - Nazaruddin -; Yuliani - (Jurnal APTEK, 2013)
This study is exploratory, which aims to particular phenomena or circumstances. Model analysis taken is to collect data, then the data is processed by quantitative classified and calculated by using a formula applied. This research was conducted with the aim of proving the influence of water flow to the radiator cooling effectiveness and calculate how much influence that occurs between the water flow to the effectiveness of the radiator. Simulator research is an engine stand of Mazda car engine in which there are few tools berhubungan.Untuk each measuring instrument can generate data measurement, components - components and gauges required including engine, radiator, fans, electric motors, pumps cooling water , flowmeter, thermometer, radiator hoses, anemometer, tachometer, stopwatchdan regulator. Effectiveness research data for decision-temperature radiator measuring the detention (holding time) for 30 minutes, with the details of the distribution (1, 5, 10, 15, 20, 25, 30) minutes. Untukputaran machines (1000, 1100, 1200, 1300, 1400) rpm ..